Data Driving Sustainability—the African Open Science Platform Project - (:unkn) unknown (My University, 2018)
Exploitation of the digital revolution offers great potential for less affluent and least economically developed countries (LEDCs) and for the attainment of the UN Sustainable Development Goals. However, LEDCs typically have poorly resourced national research systems. If they cannot participate in research based on big and open data, the gap could grow exponentially in coming years. They will be unable to collect, store and share data, unable to participate in the global research enterprise, unable to contribute as full partners to global efforts on climate change, health care, and resource protection, and unable to fully benefit from such efforts, where global solutions will only be achieved if there is global participation. Thus, both emerging and developed countries have a clear and direct interest in helping to fully mobilize LEDC science potential and thereby to contribute to achievement of the UN Sustainable Development Goals. The initiative described here (African Open Science Platform or AOSP) is directed towards minimising a divide between emerging and developed countries in what is arguably the most important current opportunity to enhance the power and efficiency of the scientific enterprise and its contribution to societal benefit.
Keywords: African Research